Theory of categories as based on the principle of acquaintance: A Critique of Jorge J. E. Gracia’s Metaphysical Neutralism - Cumpa, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In the Platonic-Aristotelian tradition, the problem of categories looms large. Plato’s Supreme Genera and Forms were attacked first by Aristotle and later by his medieval followers. These attacks constituted the triumph of individuality for the Post-Aristotelian ontologies. Empiricism, however, discovered an opponent to the basis of the Aristotelian categorial system: the bundle of properties. The pupils of Brentano analyzed this ontological novelty. Old questions were also raised again: What are the universals? Meinong and Husserl were cardinal for the birth of formal and fact ontologies. In the analytical tradition, complexes also appeared. Frege, Russell, and Polish School were central. But a problem was raised by ontologists: Where do we place the categories of set, whole, states of affairs, number, etc., in an Aristotelian ontology of substances and accidents? Type theory, formal and fact ontologies discovered the key. But ontologists faced the question: How should we understand the status of the new categories in the light of the existence-subsistence dichotomy traditionally applied to substances and universals? A discussion of these three cardinal questions for the contemporary categorial ontology is the main purpose of this paper. In order to accomplish this task, Jorge J. E. Gracia’s Aristotelian theory of categories will serve as the connecting thread of the inquiry.
Keywords: metaphysics; criteria of identification for; status of; categories; reductions; fact ontology